Program Pendampingan Belajar Siswa School From Home Era New Normal di Dusun Tempursari - Fuad Yanuar; Umi Halimah Saadah; Lina Karina Wijaya (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
The new order of life can be carried out after indicating a decrease in Covid-19. The government is facing the new normal era in education by implementing School From Home (SFH) for red zone areas. There were complaints from parents in Tempursari Hamlet who acknowledged the difficulties in assisting their children in studying at home, explaining learning materials, and dividing their time with their work. Therefore, a learning mentoring program is needed to help maximize the teaching and learning process in areas that apply SFH. The research method used is the PAR (Participatory Action Research) method through direct learning assistance to children three times a week for 30 days. This program aims to help children understand more about learning materials such as material explanations, discussions, and questions and answers. This success can be seen in mentoring learning activities during SFH and the children's enthusiasm for participating in the learning mentoring program.